Electrically controllable perchlorate removal based on poly(aniline‐co‐o‐aminophenol) doped with p‐toluene sulfonate. Issue 17 (13th January 2015) - Dai, Jiangying; Tao, Yongxin; Gu, Xiaogang; Liu, Zhong; Kong, Yong; Liu, Wenjie; Ma, Jianfeng; Wei, Yong
ABSTRACT Poly(aniline‐co‐o‐aminophenol) (PANOA) was synthesized via electrochemical copolymerization of o‐aminophenol and aniline using p‐toluene sulfonate (TSA−) as the counterion. The redox transformation of PANOA is accompanied by the exchange of anions into and out of the copolymer, and the feasibility of perchlorate (ClO4−) removal via an electrically switched ion exchange process was evaluated in this study. The results of electrochemical quartz crystal microbalance (EQCM), electrochemical impedance spectroscopy (EIS), and Fourier transform infrared spectroscopy (FTIR) demonstrated the successful release of TSA− upon reduction and uptake of ClO4− upon reoxidation of the copolymer. Also, in this work, the possible ion‐exchange mechanism of PANOA was proposed. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41895.